Failure mechanisms and behaviour of adobe masonry buildings: a case study - Canditone, C. (2023)
Non-linear static analyses are amongst engineering community one of the most common analysis approaches for the seismic assessment of existing buildings, due to a good trade-off between information needed and results produced to assess structural safety. Pushover analyses, in fact, can provide hindsight onto structural behaviour well into the non-linear range, up unto conditions of collapse initiation and structural failure. Reliable information concerning the material’s mechanical behaviour – especially in the non-linear range - is, however, required – something which is challenging for earth-based materials, such as adobe masonry, due to the acknowledged variation of their mechanical properties. In this paper, a non-linear constitutive law for adobe masonry, numerically calibrated using experimental results and defined within the widely used computer program SAP2000®, a Finite Element software package commonly used by practicing engineers for building design and structural verification, is proposed. A total strain crack-based macro-modelling approach was pursued, and mechanical properties were validated through numerical modelling and comparison with values available in literature. The proposed constitutive model, whose reliability was proven by good agreement with experimental data, is then used to evaluate the expected seismic performance of a real case study given by an adobe building in central Portugal, representative of the city of Aveiro’s earthen heritage. Therefore, starting from this application, more hindsight over the structural behaviour of Portuguese adobe masonry buildings under failure conditions was provided, also showing the implemented model suitability for large scale structural analysis in the SAP2000® software. Sensitivity analyses are run in Finite Element environment and the structural behaviour considering different boundary conditions of the building, namely isolated and aggregate conditions, is assessed through a multi-criteria approach accounting for displacement and acceleration capacity, drift levels and safety against in-plane and out-of-plane failures.